ANALISIS YURIDIS RESTORATIVE JUSTICE DALAM KEPASTIAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA - Melati, Annisa Fitri Arrum; Syawaludin, Syawaludin; Utoyo, Marsudi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang, 2023)
Abstract Restorative Justice is an approach to justice that focuses on the needs of victims and perpetrators of crime, and involves community participation, rather than implementing the principle of punishing perpetrators accompanied by the judge's considerations. Crimes committed by children are basically inseparable from various life pressures, both economic and social. As a result, quite a few children become perpetrators of crimes or crimes. This research uses a Normative Juridical research method using a statutory approach, a case approach and a conceptual approach. For children's cases, diversion must be carried out in every examination of children's cases from investigation, prosecution to examination at trial, taking into account: the category of crime, the age of the child, the results of social research from the father, the support of the family and community environment. The judge's authority is to examine and decide on children's cases at the first level with a single judge and as a facilitator in diversion. The advice that can be given is that children who commit crimes must still receive protection in the juvenile criminal justice system. One of them is implementing restorative justice using the diversion method, and judges who have the authority to examine and decide on children's cases must be proactive in encouraging restorative justice using the diversion method. Keyword : Restorative Justice, Juvenile Crimes, Judge’s Authority, Diversion